Predictors of Reduced Health‐Related Quality of Life in Adult Patients With Idiopathic Inflammatory Myopathies. Issue 11 (21st September 2017) - Feldon, Michal; Farhadi, Payam Noroozi; Brunner, Hermine I.; Itert, Lukasz; Goldberg, Bob; Faiq, Abdullah; Wilkerson, Jesse; Rose, Kathryn M.; Rider, Lisa G.; Miller, Frederick W.; Giannini, Edward H.
Abstract : Objective: Extensive studies on health‐related quality of life (HRQoL) in idiopathic inflammatory myopathies (IIMs) are lacking. Our objective was to document HRQoL and to identify factors associated with a reduced HRQoL in patients with IIM. Methods: A total of 1, 715 patients (median age 49.9 years, 70% female, 87% white) who met probable or definite Bohan and Peter criteria or Griggs criteria for myositis were included from the Myovision registry. HRQoL was ascertained using the Short Form 12 (SF‐12) health survey questionnaire. HRQoL physical component summary (PCS) and mental component summary (MCS) scores in relation to different patient and disease characteristics were compared to scores from matched normative data from the US general population and rheumatoid arthritis (RA) patients. Bivariate and multiple linear regression analyses were performed to assess the association between HRQoL and patient and disease parameters. Results: The mean SF‐12 summary scores were significantly lower in IIM patients than in the normative and RA populations. A diagnosis of inclusion body myositis, older age, patient‐reported negative effect of disease on work, presence of another co‐occurring autoimmune disease, polypharmacy, and IIM‐associated lung disease and joint involvement were significantly associated with lower PCS scores. Lower MCS scores were associated with joint involvement and a negative effect of disease on work. Conclusion: In this large study of patient‐reported outcomes in IIM, an association was found between multiple disease characteristics and reduced HRQoL, mostly in the physical domain. In the US, the HRQoL of IIM patients was found to be lower than that of the general population and RA patients.